NCMP-16. RADIATION RECALL MYELITIS FOLLOWING PACLITAXEL CHEMOTHERAPY IN METASTATIC BREAST CANCER WITH PRIOR SPINAL STEREOTACTIC BODY RADIOTHERAPY: THE FIRST REPORTED CASE. (5th November 2018) - McClelland III, Shearwood; Cooper, Paul; Acheson, Anupama; Ciporen, Jeremy; Jaboin, Jerry; Mitin, Timur
Abstract: INTRODUCTION: Stereotactic body radiotherapy (SBRT) of the spine has become an increasingly utilized modality in the United States, most commonly for metastatic disease (McClelland et al., 2017). Spinal SBRT in patients with spinal instrumentation has been sparsely examined. We report a patient who developed myelitis following spinal SBRT to a region with existing hardware. METHODS: A 55-year-old woman with Stage IV breast cancer developed a T4 vertebral body metastasis and underwent tumor debulking with posteriorly instrumented T3-T5 fusion. Postoperatively she proceeded with SBRT to the T3-T5 vertebral bodies, receiving 30 Gy in 6 Gy/fraction. Six months later, she underwent palliative RT for a new right clavicle metastasis (20 Gy in 4 Gy/fraction). She subsequently required paclitaxel chemotherapy for new liver metastases. RESULTS: Seven months following spine SBRT, shortly after having started chemotherapy she developed intractable back pain and right lower extremity numbness which improved upon receiving steroids for weekly chemotherapy; the numbness subsequently spread to her left leg. Thoracic spine MRI revealed a 1.7 cm ovoid focus of T4-T5 spinal cord enhancement with extensive surrounding cord edema extending superiorly to C6-C7, consistent with radiation myelitis. Hyperbaric oxygen moderately improved her symptoms; fortunately, she never developed motor symptomatology or bowel/bladder dysfunction. Thorough re-evaluation of the original thoracic spine SBRT plan revealed no deviations from the standard of care, nor did re-planning with alternate treatment planning software demonstrate any significant difference in maximum cord dosage than the original plan. CONCLUSIONS: The timing of symptomatology related to chemotherapy administration is consistent with radiation recall myelitis, which has yet to be reported following SBRT. Given the potentially disastrous consequences of myelitis, patients with metastatic disease previously treated with spine SBRT may be susceptible to developing radiation recall myelitis if treated with paclitaxel chemotherapy.